Organization of the Tryptophan Pathway: a Phylogenetic Study of the Fungi - Hütter, R. (1967)
The enzymes involved in tryptophan biosynthesis have been analyzed in a variety of fungal strains and a few other microorganisms. The same five biosynthetic reactions occur in all organisms tested, but differences have been found in the stability requirements for the enzymes, in their differential precipitation with ammonium sulfate, and in their sedimentation pattern after zone centrifugation. Based on the sedimentation behavior of anthranilate synthetase, phosphoribosyl-transferase, N-(5′-phosphoribosyl)-anthranilate isomerase, and indole-3-glycerophosphate synthetase, five different patterns of enzyme association could be recognized. The distribution of these patterns was used to evaluate several specific features of proposed phylogenetic relationships in the fungi. A closer relationship between Chytridiales and Aspergillales is postulated, eliminating the Zygomycetes and the Endomycetales as probable intermediates; the latter groups are considered to be sidelines. The data support the idea of a polyphyletic origin of the phycomycetes and suggest that anascosporogenous yeasts tested are related to the heterobasidiomycetes rather than to the Endomycetales. A possible sequence of changes leading to the various patterns of organization of the tryptophan pathway during the course of evolution is also proposed.